Temperature requirement for germination of conidiospores and growth of mycelia of Heterobasidion annosum s.s. and Heterobasidion parviporum - Taubert, Jasmin (SLU/Southern Swedish Forest Research Centre, 2008)
Different temperature requirements of the two species Heterobasidion annosum (Fr.) Bref. (P group) and H. parviporum Niemelä & Korhonen (S group) should explain why the distribution areas are different in Scandinavia despite of a wide range of distribution of their host species Picea abies and Pinus sylvestris up to 68°N. Temperature ranges of P and S were observed. Germination percent, length of the germination tubes of the conidiospores and growth rate of the mycelia were measured for 6 individual strains of the S and P group, respectively. When sampled, mycelial strains of the S group showed a significantly faster growth rate at 22°C compared to the strains of the P group. Germination percent and length of the germination tubes of the conidiospores were insignificant at all temperatures. In conclusion, growth rate of the S group increased with temperature until 27°C and increase of the growth rate of the P group stagnated after 22°C. The S group had a wider temperature range than the P group.